Interventions to facilitate return to work in adults with chronic non-malignant pain: a protocol for a systematic review and network meta-analysis. Issue 11 (16th November 2020) - Björk, Mathilda; Gerdle, Björn; Liedberg, Gunilla; Svanholm, Frida; Solmi, Marco; Thompson, Trevor; Chaimani, Anna; Dragioti, Elena
Abstract : Introduction: Work absenteeism due to chronic non-malignant pain (CNMP) is a major societal and individual cause of concern that requires effective treatments. Objective: We present a protocol for a systematic review and network meta-analysis (NMA) aiming to compare available interventions for return to work (RTW) in adults with CNMP. Methods and analysis: PubMed, Embase, PsycINFO, Web of Knowledge and Cochrane Central Register of Controlled Trials databases will be searched till 31 August 2020 for randomised controlled trials (RCTs) examining interventions for RTW outcomes among patients with CNMP. Two independent investigators will search the databases, perform data extraction and assess the methodological quality of the selected RCTs. The primary outcome will be RTW, if possible, full-time or part-time after work absence due to chronic pain from baseline to the last available follow-up. Secondary outcomes will include self-reported workability or work capacity, or self-reported physical functioning and quality of life as measured by any validated scale. Pairwise meta-analysis and NMA will be conducted for each outcome using a random-effects model. For the primary outcomes, we will also obtain the ranking of all competing interventions within each NMA using surface under the cumulative ranking curve. The assumption of coherence (ie, that direct and indirect evidence are in statistical agreement) will be examined using both a local and a global approach. We will also conduct subgroup and meta-regression analyses, whenever feasible, to investigate the unexplained variation in effect size. The comparison-adjusted funnel plot will be used to evaluate small-study effects. The overall quality of evidence will be rated with the Confidence in Network Meta-Analysis tool. Data analysis will be conducted using Stata V.16.0. Ethics and dissemination: This systematic review does not require ethical approval since it will not disseminate any private patient data. The results of this study will be disseminated through peer-reviewed publication. PROSPERO registration number: CRD42020171429.